UPAYA PENINGKATAN KETRAMPILAN MENYUSUN LAPORAN KEUANGAN BAGI PENGURUS KOPERASI WANITA (KOPWAN) DESA BAMBANG KECAMATAN TURI LAMONGAN - Zakaria Anshori; Leni Faizatus Suniah (Media Mahardhika, 2020)
This community service activity is carried out at the Lintang Jaya Women's Cooperative Management (Kopwan), which is one of the places for economic activity in Bambang Village, Turi District. This community service aims to provide training and assistance in the preparation of cooperative financial reporting. The methods used to realize this community service program are (1) the preparation stage, (2) the implementation stage, (3) the evaluation stage. Broadly speaking, this training activity can be declared successful, seen from the enthusiasm of the cooperative management during the training process and assistance in preparing financial reports. In addition, this service activity can contribute to increasing the knowledge and skills of cooperative managers in preparing cooperative financial reports in accordance with applicable accounting standards.